Regarding the prospects of using Lactobacillus-based probiotics, D-mannose and cranberry extracts in therapy of urinary tract infections - O. A. Gromova; I. Yu. Torshin (Акушерство, гинекология и репродукция)
Antibiotics are most often used to combat urinary tract infections (UTIs). Taking into account the side effects related to antibiotic therapy, existing antibiotic-resistant strains of uropathogens, as well as the low effectiveness of the vast majority of antibiotics against bacterial agglomerations (biofilms), a search for alternative approaches to treat UTIs is highly relevant. One of the important in such search is presented by use of nutraceuticals – D-mannose (prevents interaction between pathogenic E. coli strains and the urothelium, destroys bacterial biofilms), Lactobacilli (prevents formation of bacterial pathogen biofilms, normalizes human microbiome, alleviates inflammation) and standardized cranberry extracts (inhibits uropathogen adhesion, exerts anti-inflammatory action). The results from basic and clinical studies suggest not only about high safety of such pharmaconutraceutical support of UTIs therapy, but also the effectiveness of separate and combined use of such nutraceuticals comparable to that of antibiotics, especially in treatment of uncomplicated UTIs forms